1972
DOI: 10.1111/j.1471-4159.1972.tb05088.x
|View full text |Cite
|
Sign up to set email alerts
|

ZINC IN MATURING RAT BRAIN: HIPPOCAMPAL CONCENTRATION AND LOCALIZATION1

Abstract: —Alterations in the localization and concentration of zinc in the hippocampus and in other regions of rat brain were studied during postnatal maturation. Histochemical observations indicated increasing levels of zinc in the hippocampal mossy fibre layer at about 20 days of age. Between 18 and 22 days, hippocampal levels of zinc increased by 35 per cent to reach adult levels (121 ng/mg of protein). After subcellular fractionation, more than one‐half of the hippocampal zinc was found in the first pellet (P1; 108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(37 citation statements)
references
References 3 publications
3
34
0
Order By: Relevance
“…Zinc is known to be preferentially concentrated in specific neuronal structures including the hippocampus and cortex (Crawford & Connor, 1972;Donaldson et al, 1973;Friedman & Price, 1984). Zinc can also be taken up into neuronal tissue (Wolf et al, 1984;Wensink et al, 1988) and high concentrations have been observed in nerve terminals, particularly in the hippocampal mossy fibre terminations (Ibata & Otsuka, 1969;Perez-Clausell & Danscher, 1985) and also within terminal boutons in many other regions of the telencephalon (Perez-Clausell & Danscher, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc is known to be preferentially concentrated in specific neuronal structures including the hippocampus and cortex (Crawford & Connor, 1972;Donaldson et al, 1973;Friedman & Price, 1984). Zinc can also be taken up into neuronal tissue (Wolf et al, 1984;Wensink et al, 1988) and high concentrations have been observed in nerve terminals, particularly in the hippocampal mossy fibre terminations (Ibata & Otsuka, 1969;Perez-Clausell & Danscher, 1985) and also within terminal boutons in many other regions of the telencephalon (Perez-Clausell & Danscher, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…(Curtis & Gynther, 1987) and also on cultured hippocampal neurones of the mouse (Westbrook & Mayer, 1987). These studies of zinc on GABA function suggest that one possible role for the endogenous zinc in the central nervous system (CNS) (Crawford & Connor, 1972;Donaldson et al, 1973) may be to interact with, or modulate the GABAA-receptor. However, due to the apparent variety of effects zinc is deemed to produce on neuronal GABA responses, we have reinvestigated the action of this divalent cation on GABA responses recorded from dissociated and intact sympathetic neurones and brain slices.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the reagents treated this way contained less than 0.02 pM zinc. Initial metal analyses were made on 0.5-ml samples using a flame method as previously described [25]. More detailed studies were made on 3-pl samples injected into the atomization furnace.…”
Section: Metal Analysismentioning
confidence: 99%
“…Zinc is centrally involved in multiple human systems (133), induding GABA and other neurotransmitter enabling (24,45,(134)(135)(136)(137), and in sequestering and defense against heavy metals and chemicals (138). Gestational Zn deficiency appears to damage hippocampal and other functions (44,45,139,140). Chronic Zn deficiency reduces the IRA by deactivation of thymulin (133,(141)(142)(143)(144) (19,(145)(146)(147)(148) (158), including the brain (158), and it can cross the blood-brain barrier (159).…”
Section: Individual Ids Descriptionsmentioning
confidence: 99%